Association of Arterial pH With Hemodynamic Response to Vasopressin in Patients With Septic Shock: An Observational Cohort Study. (8th February 2022) - Bauer, Seth R.; Sacha, Gretchen L.; Siuba, Matthew T.; Lam, Simon W.; Reddy, Anita J.; Duggal, Abhijit; Vachharajani, Vidula
Abstract : OBJECTIVES: Vasopressin is reported to retain vasoconstrictive activity in the setting of acidemia, but preclinical models are inconsistent and studies have not evaluated the clinical effectiveness of vasopressin based on arterial pH. This study sought to determine the association between arterial pH and blood pressure after vasopressin initiation in septic shock. DESIGN: This retrospective, multicenter, observational cohort study evaluated the association of arterial pH at the time of vasopressin initiation with hemodynamic response to vasopressin and change in catecholamine dose after vasopressin initiation. Hemodynamic response was defined as a catecholamine dose decrease with mean arterial pressure greater than or equal to 65 mm Hg at 6 hours after vasopressin initiation. SETTING: Patients from eight hospitals in a health system were evaluated. PATIENTS: Patients with septic shock initiated on vasopressin as a catecholamine adjunct between January 2012 and November 2017 were screened for inclusion. INTERVENTIONS: None. MEASUREMENTS AND MAIN RESULTS: A total of 1, 350 patients were included. At the time of vasopressin initiation patients were severely ill with arterial pH 7.28 ± 0.13, Sequential Organ Failure Assessment 14.1 ± 3.5, lactate 5.6 ± 4.6 mmol/L, and norepinephrine-equivalent catecholamine dose 32.3 ± 25.4 µg/min. After adjusting for lactate and Sequential Organ Failure Assessment with multivariable logistic regression, lower arterial pH was independently associated with lower odds of hemodynamic response to vasopressin (for each 0.1 unit arterial pH was below 7.40, response odds ratio 0.79; 95% CI, 0.72–0.87). For each 0.1 unit the pH was below 7.40 at vasopressin initiation, the norepinephrine-equivalent catecholamine dose increased by 1.5 µg/min (95% CI, 0.5–2.5 µg/min) at 1 hour, and increased by 2.5 µg/min (95% CI, 1.4–3.5 µg/min) at 6 hours after vasopressin initiation. CONCLUSIONS: Compared with higher arterial pH, patients with septic shock and low arterial pH had lower odds of vasopressin response and higher catecholamine doses after vasopressin initiation. Similar to other vasopressors, the clinical effectiveness of vasopressin appears to be impaired in the setting of acidemia.